Secular trends in procedural stroke or death risks of stenting versus endarterectomy for symptomatic carotid stenosis: a pooled analysis of randomized trials - Müller, Mandy D.; Felten, Stefanie Noel von; Algra, Ale J.; Becquemin, Jean-Pierre; Bulbulia, Richard; Calvet, David; Eckstein, Hans-Henning; Fraedrich, Gustav; Halliday, Alison; Hendrikse, Jeroen; Howard, George; Gregson, John; et al. (Circulation. Cardiovascular interventions, 2019)
Background:Over the past decades, stroke risk associated with carotid disease has decreased, reflecting improvements in medical therapy and a more rigorous control of vascular risk factors. It is less clear whether the procedural risk of carotid revascularization has declined over time.Methods:We analyzed temporal changes in procedural risks among 4597 patients with symptomatic carotid stenosis treated with carotid artery stenting (n=2326) or carotid endarterectomy (n=2271) in 4 randomized trials between 2000 and 2008, using generalized linear mixed-effects models with a random intercept for each source trial. Models were additionally adjusted for age and other baseline characteristics predicting treatment risk. The primary outcome event was any procedural stroke or death, occurring during or within 30 days after revascularization.Results:The procedural stroke or death risk decreased significantly over time in all patients (unadjusted odds ratio per year, 0.91; 95% CI, 0.85-0.97; P=0.006). This effect was driven by a decrease in the carotid endarterectomy group (unadjusted odds ratio per year, 0.82; 95% CI, 0.73-0.92; P=0.003), whereas no significant decrease was found after carotid artery stenting (unadjusted odds ratio, 0.96; 95% CI, 0.88-1.04; P=0.33). Carotid endarterectomy patients had a lower procedural stroke or death risk compared with carotid artery stenting patients, and the difference significantly increased over time (interaction P=0.031). After adjustment for baseline characteristics, the results remained essentially the same.Conclusions:The risk of stroke or death associated with carotid endarterectomy for symptomatic carotid stenosis decreased over an 8-year period, independent of clinical predictors of procedural risk. No corresponding reduction in procedural risk was seen in patients treated with stenting.Clinical Trial Registration:URL: https://www.clinicaltrials.gov; http://www.isrctn.com. Unique identifier: NCT00190398 (EVA-3S), NCT00004732 (CREST), ISRCTN57874028 (SPACE), and ISRCTN25337470 (ICSS).